Interval between the application of metsulfuron-methyl and sowing soybean in different production environments - Guerra, Naiara; Oliveira Neto, Antonio; Schmitt, Jaqueline; Carneiro, Adriano; Kopko, Lucas; Jochem, Wilian (Revista Ciência Agronômica, 2020)
The persistence of herbicides in the soil is extremely important for controlling weeds during the critical period of weed interference, and for determining which substitute crops might be sown. The aim of this study was to evaluate the effect of metsulfuron-methyl when applied at different times in relation to sowing soybean, seeking to determine a safe interval between its application and sowing the legume under different conditions of soil and climate. Two experiments were conducted, one in the district of Campo Mourão in the state of Paraná (PR) (2014/15 crop) and the other in Curitibanos in the state of Santa Catarina (SC) (2015/16 crop). Both experiments were carried out in a randomised block design with four replications. The treatments were arranged in a 2 x 6 + 1 factorial scheme, where factor A represented two doses of metsulfuron-methyl (1.98 and 3.96 g ha-1), and factor B six different intervals between applying the metsulfuron-methyl and sowing the soybean (0, 15, 30, 45, 60 and 75 days after application - DAA), in addition to a control without the application of herbicide, to serve as a standard for comparison. The following were evaluated: percentage phytotoxicity, plant height, stand, number of pods per plant, 100-grain weight and productivity. A difference was seen in the persistence of metsulfuron-methyl for the experiments in Campo Mourão PR, and Curitibanos SC, and was greater for Campo Mourão. The safe interval between applying the metsulfuron-methyl and sowing the soybean was 17 days for the experiment in Curitibanos and 40 days for Campo Mourão. Precipitation volume, pH and organic matter are the main factors to possibly have influenced this interval.